Vitamin D kinetics in nonpregnant and pregnant women after a single oral dose of trideuterated vitamin D3. Issue 216 (February 2022) - Best, Cora M.; Sherwood, Robert; Novotny, Janet A.; Zhang, Sheng; Pressman, Eva K.; O'Brien, Kimberly O.
Highlights: Nonpregnant and pregnant women ingested a 25 μg dose of deuterated (d3) vitamin D3 . We assessed the serum appearance and disappearance of d3-vitamin D3 and d3-25(OH)D3 . Serum vitamin D binding protein (DBP) concentration was higher in pregnant women. Serum DBP concentration was positively associated with the d3-25(OH)D3 AUC. Abstract: The plasma pool of the hormone 1, 25-dihydroxyvitamin D (1, 25(OH)2 D) is increased throughout most of human pregnancy. Mechanisms behind this adaptation are unclear, in part due to limited data on vitamin D kinetics during pregnancy. Stable isotopes make it possible to study vitamin D kinetics in vulnerable study populations like pregnant women. We conducted a pilot study of vitamin D kinetics in nonpregnant and pregnant women. We evaluated a clinical protocol and developed analytical methods to assess the serum appearance and disappearance of trideuterated vitamin D3 (d3-vitamin D3 ) and trideuterated 25-hydroxyvitamin D3 (d3-25(OH)D3 ) after a single oral dose of 25 μg of [6, 19, 19- 2 H]-vitamin D3 (d3-vitamin D3 ). Blood was collected at baseline and 2, 4, 6, 24, 168, 264, and 456 hours post-dosing. We then described the serum kinetic profiles of d3-vitamin D3 and d3-25(OH)D3 in nonpregnant and pregnant women. Serum kinetic profiles of d3-vitamin D3 and d3-25(OH)D3 followed a time course in line with previous pharmacokinetic studies. There was marked variability between participants in the area under the concentration-time curve (AUC) of d3-25(OH)D3 over the 20-day study period. This AUC of d3-25(OH)D3 was positively correlated with the serum vitamin D binding protein (DBP) concentration, which was higher in pregnant compared with nonpregnant women. The mean serum half-life of 25(OH)D3 was longer but not significantly different in pregnant women (18.8 days) compared with nonpregnant women (13.6 days). Our pilot study demonstrated that a single oral dose of 25 μg of d3-vitamin D3 can be used to study vitamin D kinetics. Serum DBP concentration is an important predictor of vitamin D kinetics, and more research is needed to fully understand the significance of elevated DBP concentration during pregnancy.